Review and Prospect on the Research of 5G Spectrum - Jian Fang; Jingchun Li; Biao Huang; Yan Feng (Dianxin kexue)
Firstly, the future framework of 5G spectrum was analyzed based on the application scenarios suggested by the ITU-R recommendation on 5G vision. Next, from the aspects of spectrum requirement, candidate band and sharing study, the core contents of 5G spectrum work and the difference of 5G spectrum and previous research were discussed. Then, by fully investigating the current research development of 5G spectrum, the future research area was proposed. Finally, the impact and challenges on radio management work were put forward.